Chemisorbed nickel catalyst for the production of SWCNTs with a very narrow size distribution. Issue 12 (27th November 2013) - Devaux, Xavier; Tsareva, Svetlana Yu.; Carteret, Cédric; Dossot, Manuel; Grégoire, Brian; Humbert, Bernard; Mevellec, Jean‐Yves; McRae, Edward; Aranda, Lionel; Lamouroux, Emanuel; Fort, Yves
<x xml:space="preserve">Abstract</x> The synthesis of single‐walled carbon nanotubes (SWCNTs) with the narrowest possible diameter distribution is a challenging undertaking in carbon nanoscience, which can be overcome through the fabrication of monodisperse catalytic nanoparticles. A technique is presented here to approach the diameter control of SWCNTs using a chemisorbed nickel acetylacetonate monolayer at the surface of silica. We show by Fourier transform infrared spectroscopy and thermogravimetry coupled with mass spectroscopy that a monolayer of nickel acetylacetonate is anchored with the silanol groups at the surface of the substrate. After thermal decomposition, the nickel remains bonded with these silanol groups, resulting in a good dispersion of the nickel over the silica surface. Using this catalyst, SWCNTs with a narrow diameter distribution were synthesized at moderate temperature. This opens new perspectives for the fabrication of uniform‐diameter carbon nanotubes.